NEEDS ANALYSIS OF DEVELOPING INSTRUCTIONAL TEACHING PLAN IN WATER CONSERVATION FOR PRIMARY SCHOOL - Asnida Ismail; Nor Asniza Ishak (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study utilizes a qualitative methodology to explore the development needs of instructional teaching plans to improve knowledge, attitudes, and practices related to water conservation among primary school students. Through semi-structured interviews and drawing analysis, participants are selected from three primary schools in Penang’s north district using purposive sampling. This approach ensures the gathering of detailed and pertinent data by involving four science teachers and five students who offer insights into the instructional requirements and obstacles encountered in teaching water conservation. The primary objective is to grasp the specific needs, perspectives, and learning preferences of both students and teachers. It facilitates the creation of instructional materials that resonate with the target audience, leading to increased engagement and effectiveness. The research is motivated by the critical role of needs analysis in guiding educational content development, underscoring the significance of aligning instructional materials with the distinct demands of the educational setting. By manually analyzing interview data thematically, the study sheds light on issues such as time constraints, resource shortages, student readiness, teaching methodologies, and student needs. Additionally, drawing analysis reveals prevalent misconceptions, indicating a limited understanding of pollution causes/effects and conservation concepts. This investigation adds to educational research and seeks to enhance the implementation and impact of water conservation practices in primary education.